2021
DOI: 10.1016/j.heliyon.2021.e08259
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of midgut microbiota in laboratory-colonized and field-collected Aedes albopictus (Diptera: Culicidae): A preliminary study

Abstract: Aedes (Ae.) albopictus is an important vector for many pathogens. Previous studies have revealed a role for midgut bacteria during pathogen infection in mosquitoes; however, studies of Ae. albopictus midgut bacteria are limited. We examined the diversity of midgut bacteria in female laboratory-colonized and field-collected Ae. albopictus. A total of 31 bacterial genera were identified representing 10 and 28 genera of laboratory-colonized and fieldcollected Ae. albopictus, respectively. The predominant bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…The higher abundance of Serratia in bacterial communities of larval stages, particularly in Ae. albopictus , contrasts with previous findings of this genus being abundant in adult mosquito reproductive organs [ 31 , 37 , 48 , 49 ] and midgut [ 38 ].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The higher abundance of Serratia in bacterial communities of larval stages, particularly in Ae. albopictus , contrasts with previous findings of this genus being abundant in adult mosquito reproductive organs [ 31 , 37 , 48 , 49 ] and midgut [ 38 ].…”
Section: Discussioncontrasting
confidence: 95%
“…Particularly, Proteobacteria accounted for more than 80% of bacteria in field-collected Ae. albopictus in one previous study in Thailand [ 38 ]. The phylum Firmicutes was also very abundant in the Ae.…”
Section: Discussionmentioning
confidence: 99%
“…These differences between field-collected and colonized mosquitoes have already been reported for other mosquito species. The bacterial diversity in field-collected Aedes albopictus mosquitoes was found to be much higher compared to colonized lines [ 29 ]. Additionally, it was demonstrated that colonized Aedes aegypti mosquitoes are less genetically variable than their field counterparts [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti collected in Houston, TX, United States [ 19 ]; Serratia marcescens was found in Ae. albopictus collected in Sing Bur Province of Thailand, and absent in mosquitoes of this species collected in Chumphon and Yala Provinces [ 20 ]. The occurrence of Serratia in Ae.…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies focusing on bacteria and mosquitoes is increasing. Among these studies are: understanding the acquisition and composition of the microbiota [ 4 , 20 ], its relationship with vector capacity [ 30 ], its importance in the modulation of pathogen development in mosquitoes [ 31 ], and how bacterial interactions can modulate the bacterial community in the mosquito [ 19 ]. Despite this increasing interest in mosquito microbial investigations and the epidemiological importance of the Vale do Ribeira region as a potential source of sylvatic arboviruses and vertebrate reservoirs, little is known about the microbiota in mosquito populations inhabiting the southeastern Atlantic tropical rain forest, São Paulo, Brazil.…”
Section: Introductionmentioning
confidence: 99%